Penerapan Terapi Musik Klasik Dalam Menurunkan Nyeri Pada Pasien Ca Mammae Literaure Review - Rizqi Apriani Pujianto; Ricky Zainuddin (Poltekkes Kemenkes Surakarta, 2019)
Background: Music therapy is a form of therapy in the health sector using music and music activities to address various issues. Empirical evidence supports the therapeutic use of classical music in a variety of conditions including psychiatric disorders, medical problems, physical disabilities, sensory disturbance, developmental disabilities, aging problems, increase the concentration of learning, support physical exercise, reducing stress and anxiety, as well as additional treatment in cancer patients and management pain. This article analyzes the application of music therapy to reduce pain scale and by reviewing the results of this study. Methods: This study explores quantitative evidence published in electronic databases such as Pubmed, Google Scholar. Results: Research shows that a significant increase occurred in the post-intervention in reducing the pain scale for participants who received the Classical Music Therapy as compared to all the controls. Conclusion: The results showed that the classical music therapy is very useful additional treatment to reduce the scale of pain in cancer patients who have never undergone chemotherapy and nurses must be trained to perform classical music therapy.